Регуляція та оптимізація функціональних станів особи - Буняк, Надія; Неплохов, Сергій (Психологія і суспільство, 2024)
У статті репрезентовано зміст регуляції та оптимізації функціонального стану особи на трьох рівнях – психологічному, психофізіологічному та поведінковому. Обґрунтовано важливість комплексного підходу до вирішення проблемного питання повноти розуміння вказаного стану як об’єднавчого показника, котрій є змога регулювати, оптимізувати його перебіг й у такий спосіб запобігти розвитку несприятливих функціональних станів працівників. У прикладному аспекті зазначено, що на сьогодні психологічні теорія і практика пропонує дієві шляхи попередження (профілактики) незручних (негативних) для кожної окремої особи функціональних станів, передусім задля збереження її фізичного та психічного здоров’я. Упорядковано та детально описано функціональні стани особистості залежно від набору критеріїв – надійності та цінності діяльності, адекватності відповідної реакції людини вимогам праці та системності характерних ознак-властивостей її успішності і результативності. При цьому підкреслено, що за інтегральний критерій оцінювання фактичного індивідуального здоров’я особи використовується функціональний стан її органів і систем організму (серцево-судинної, дихальної, центральної нервової, крові тощо). Сутнісно визначено, що психічний аспект функціонального стану полягає у почуттях і переживаннях, а фізіологічний – у зміні цілої низки функцій, котрі виражаються соціально зумовленою поведінковою, усвідомленою руховою чи іншою діяльністю. Висвітлено та описано стани, котрі знаходять несприятливе відображення на комплексному процесі, що охоплює всі вітальні виміри існування особи (стрес, дистрес, нервово-психічне напруження, втома, хронічна втома, перевтома, монотонія), шляхи та засоби їх психологічної оптимізації і профілактики, котрі є нагальними і вельми перспективними.The content of egulation and optimization of the functional personality state at the following three levels: psychological, psychophysiological and behavioral is presented in this paper. The need of comprehensive approach to the solution of the problem concerned in this paper is substantiated, since the functional personality state is an unifying indicator, however there are diverse considerations regarding both the concept of «functional state» and the factors on which it depends, and what personality characteristics are taken into account, which levels of functional state are distinguished, in what way it can be regulated and optimized, and howto prevent the development of unfavorable functional states. It is noted that the identification of all functional personality states is carried out not only in order to find appropriate ways of their evaluation, but also has direct practical significance. In practical terms, this means to find ways for warning (preventing) uncomfortable (negative) functional states for each individual personality in order to maintain his or her physical and mental health. The functional personality states are arranged and described in detail depending on the variety of criteria – reliability and activity price, adequacy of the person’s response to the requirements of activity and according to the characteristic features. Moreover, it is noted that the functional state of organs and systems of the human body (cardiovascular, respiratory, central nervous, blood, etc.) is used as the criterion for actual individual health evaluation. Quite simple and clear interpretation of the distinction between three levelsof the functional personality state, i. e. Any state of the personality both feelings and activity of the body functional systems, expressed in behavior is revealed and completely supported by the author. Or, in other words, it can be expressed in the following way: mental (psychological) aspect of the state consists of feelings and experiences, physiological aspect includes changes of the whole range of functions, which are expressed by socially conditioned behavioral, motor or other activities, being a conscious personality. The states that adversely affect the complex process covering all aspects of the person’s existence (stress, distress, neuropsychological stress, tiredness, chronic tiredness, exhaustion, monotony), ways and means of their psychological optimization and prevention, which are timely and very promising are considered and characterized in this paper.